Bragança an aging district and neurodegenerative diseases” - Fernandes, Adília (2021)
The territory is considered low density due to criteria related to demographic, economic, urban, institutional and relational aspects [2]. The total number of elderly people in the district is 124121 [4]. A marked loss of population and a continuous and marked aging has occurred in this district. To compare the aging index in Bragança district with the national one and identify the most prevalent neurodegenerative diseases in the district. Descriptive statistics were used to synthesize the demographic data collected from INE [3] and the epidemiological ones of neurodegenerative diseases active diagnoses provided by the Northeast Local Health Unit [5].